2018
DOI: 10.1016/j.neuron.2018.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Pauses in Cholinergic Interneuron Activity Are Driven by Excitatory Input and Delayed Rectification, with Dopamine Modulation

Abstract: SummaryCholinergic interneurons (ChIs) of the striatum pause their firing in response to salient stimuli and conditioned stimuli after learning. Several different mechanisms for pause generation have been proposed, but a unifying basis has not previously emerged. Here, using in vivo and ex vivo recordings in rat and mouse brain and a computational model, we show that ChI pauses are driven by withdrawal of excitatory inputs to striatum and result from a delayed rectifier potassium current (IKr) in concert with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 57 publications
1
83
1
Order By: Relevance
“…Together, our results indicate that the initial responsiveness of the CINs is not altered, but their overall excitability is reduced due to stronger firing rate adaptations in the absence of Er81 (Figure 3D). It has been shown that CIN firing rate is controlled by the large, calcium-dependent delayed rectifier current I Kr (Zhang et al, 2018) (Wilson and Goldberg, 2006). Therefore, the observed differences ( Figure 3B) might be due to an increase in the I Kr current in the Er81 cKO conditions.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Together, our results indicate that the initial responsiveness of the CINs is not altered, but their overall excitability is reduced due to stronger firing rate adaptations in the absence of Er81 (Figure 3D). It has been shown that CIN firing rate is controlled by the large, calcium-dependent delayed rectifier current I Kr (Zhang et al, 2018) (Wilson and Goldberg, 2006). Therefore, the observed differences ( Figure 3B) might be due to an increase in the I Kr current in the Er81 cKO conditions.…”
Section: Introductionmentioning
confidence: 92%
“…In order to decipher the molecular mechanisms behind this regulation, we first analysed the expression of previously identified I Kr mediators in CINs, the KCNQ2/3 hetero-tetramer channels (Zhang et al, 2018). We found a significant decrease in KCNQ2 mRNA levels ( Figure 3H), without any change in KCNQ2 protein levels (Figure 3I & J) between the P30 control and Er81 cKO mice.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations